Silicate mineralogy of basalts at DSDP Leg 54 Holes - Robert N Thompson; Susan E Humphris (PANGAEA, 1980)
Basalts drilled from the East Pacific Rise, OCP Ridge, and Siqueiros fracture zone during Leg 54 are texturally diverse. Dolerites are equigranular at Sites 422 and 428 and porphyritic, with phenocrysts of plagioclase (An69.73) and Ca-rich clinopyroxene (Ca42Mg48Fe10) at Site 427. The East Pacific Rise lavas and some of those from the OCP Ridge are fine-grained and porphyritic. The majority of the large crystals are clustered skeletal glomerocrysts of plagioclase An64-77), together with olivine (Fo80-87), Ca-rich clinopyroxene, or both. Euhedral phenocrysts of plagioclase, together with olivine, Carich clinopyroxene, and Cr-Al spinel in some cases, occur in most of the fine-grained lavas. These phenocrysts are small (maximum dimension <1 mm in all but one sample), sparse (combined modal amount <1% in all samples), and distinctive from the megacrysts which characterize many ocean-floor lavas. In two East Pacific Rise lavas, zoned plagioclase (An83 cores) is the sole phenocryst phase. In other porphyritic lavas from all the main East Pacific Rise and OCP Ridge units drilled during Leg 54, the plagioclase phenocrysts contain cores of bytownite (An79-87) surrounded by more-sodic feldspar (An67-77). Core/rim relationships vary from continuous normal zoning, through discontinuous zoning, to extensive resorption of the calcic cores in some samples. The compositions of the plagioclase calcic cores are systematically related to those of the glomerophyric plagioclase and olivine in the lavas containing them. Furthermore, only one compositional population of calcic cores occurs in each rock. The possible causes of these relationships are far from clear. Magma mixing, although superficially applicable, is inconsistent with important aspects of the phenocryst mineralogy of these particular lavas. A more satisfactory model to explain both phenocryst zoning and rapid glomerocryst growth immediately before extrusion may be constructed by postulating influx of water into the upwelling magmas within Layer 3 of the oceanic crust beneath the East Pacific Rise, and subsequent loss of part of this water during effervescence within feeder dykes between Layer 3 and the ocean floor. It is shown that this model is fully consistent with published data on water and carbon dioxide contents and ratios in the pillow-margin glasses, vesicles, and phenocryst inclusions of ocean-floor basalts. The evidence for the precipitation of plagioclase- dominated crystalline assemblages from these magmas in the upper part of Layer 3 is concordant with recent geophysically based modeling of the structure of the East Pacific Rise. Calcium-rich clinopyroxenes in dolerites from the OCP Ridge and Siqueiros fracture zone show radial, oscillatory, and sector-zoning. In Sample 428A-5-2 (Piece 5a), the compositional trends resulting from this zoning closely resemble those of the pyroxenes in some lunar lavas. The controls on crystallization of interstitial pigeonite - epitaxial upon augite - in this rock are discussed. Both sector-zoning of the augite and nucleation of pigeonite within microvolumes of magma with a low Ca(Mg + Fe) ratio appear to be important factors.
Supplement to: Thompson, RN; Humphris, SE (1980): Silicate mineralogy of basalts from the East Pacific Rise, OCP Ridge, and Siqueiros fracture zone: Deep Sea Drilling Project, Leg 54. In: Rosendahl, BR; Hekinian, R; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 54, 651-669, https://doi.org/10.2973/dsdp.proc.54.126.1980